Mobile Casier System untuk Usaha Kecil “Kaki Lima” Berbasis Android pada Waralaba Kebab Kings - Nugroho, Adi; Sutanto, Teguh; Sukmaaji, Anjik (JAVA Journal of Electrical and Electronics Engineering, 2015)
Kebab Kings is a franchise company that operates in the field of business, namely fast food kebabs and burgers. The company is experiencing difficulty in improving the speed of service to customers, calculate the amount of raw materials used and to analyze the amount of revenue and the level of the crowd from each outlet is owned certainty because it can influence the decisions and policies of the management company for the future. The Cashier Android-Based Applications Case Study In Kebab Kings Indonesia is very easy to use because it displays a user friendly interface . The software used is the Android SDK (Software Development Kit) and supported by AVD (Android Virtual Device) with version 3.0 (Honeycomb), which serves to develop algorithms that are built using the Android Studio and Sublime Text 2 as an editor to write a script